Menanamkan Pemahaman Profil Pelajar Pancasila untuk di Implementasikan di Jenjang Sekolah SD, SMP di Desa Makmur Kecamatan Pangkalan Kerinci Kabupaten Pelalawan Provinsi Riau - Erlinda, Sri; Hafis, Muhammad Al; Andreyan, Dewi; Faradilla, Nurrahma; Billah, Ladya Lavia; Siahaan, Marsa Adelia Br; Amalia, Rahma; Reka, Sulistia; Sukraini, Sukraini; Putri, Puji Oktaliani (Yayasan Daarul Huda Kruengmane, 2024)
As the educational landscape continues to evolve, understanding and implementing Pancasila values among students has become increasingly vital. This study aimed to instill the values of Pancasila in elementary and middle school students in Desa Makmur, Kecamatan Pangkalan Kerinci, Kabupaten Pelalawan, through an innovative approach using inspirational video stories as a learning medium. The method used was participatory action research, with activities held in MDTA, elementary schools (SD), and middle schools (SMP) in Desa Makmur. The results showed that this method effectively increased students' understanding of Pancasila principles, fostering values such as teamwork, independence, and critical thinking. The video-based learning was particularly well-received, promoting student engagement and reflection on real-life applications of Pancasila values. This program represents an essential step toward character building and fostering the next generation of leaders aligned with Pancasila principles.